Forgiveness of others and subsequent health and well-being in mid-life: a longitudinal study on female nurses - Katelyn N. G. Long (BMC Psychology, 2020)
Abstract Background Forgiveness is a concept of growing interest within psychology and of potential relevance to public health. While there has been increasing evidence suggesting positive associations between forgiveness of others and a range of psychosocial well-being and mental health outcomes, its associations with health behaviors and physical health are less clear. Methods This study used longitudinal data from the Nurses’ Health Study II (2008 Trauma Exposure and Post-traumatic Stress Supplementary Survey to 2015 questionnaire wave, N = 54,703), to conduct an outcome-wide analysis among a cohort of female nurses in the United States (age range: 43–64 years). The study prospectively examines the association between spiritually motivated forgiveness of others and a number of of subsequent psychosocial well-being, mental health, health behavior, and physical health outcomes in midlife. A set of linear, logistic, and Poisson regression models were used to regress each outcome on forgiveness in separate models. Sociodemographic factors, prior religious service attendance, and prior values of all outcome variables were controlled for wherever data were available. To account for multiple testing, we performed Bonferroni correction. Results Forgiveness was associated with subsequent improved psychosocial well-being and reduced psychological distress outcomes in a monotonic pattern. For instance, the top versus bottom level of forgiveness was associated with substantially higher levels of subsequent positive affect (β = 0.18, 95% CI: 0.15, 0.21) and social integration (β = 0.15, 95% CI: 0.13, 0.17), and was inversely associated with several indicators of subsequent psychological distress such as depressive symptoms (β = − 0.16, 95% CI: − 0.19, − 0.14). However, in this sample, there was little evidence that forgiveness was associated with health behaviors or physical health outcomes. Discussion This study suggests that forgiveness may be a health asset for promoting population mental health and psychosocial well-being, and moreover may also be understood as a good in itself. Further investigation on the dynamics between forgiveness and physical health is warranted to explore the discrepancy between the results here and some past research.